Site-specific Proteasome Phosphorylation Controls Cell Proliferation and Tumorigenesis - Guo, Xing (Nat Cell Biol, 2015)
Despite the fundamental importance of proteasomal degradation in cells, little is known about whether and how the 26S proteasome itself is regulated in coordination with various physiological processes. Here we show that the proteasome is dynamically phosphorylated during cell cycle at Thr25 of the 19S subunit Rpt3. CRISPR/Cas9-mediated genome editing, RNA interference and biochemical studies demonstrate that blocking Rpt3-Thr25 phosphorylation markedly impairs proteasome activity and impedes cell proliferation. Through a kinome-wide screen, we have identified dual-specificity tyrosine-regulated kinase 2 (DYRK2) as the primary kinase that phosphorylates Rpt3-Thr25, leading to enhanced substrate translocation and degradation. Importantly, loss of the single phosphorylation of Rpt3-Thr25 or knockout of DYRK2 significantly inhibits tumor formation by proteasome-addicted human breast cancer cells in mice. These findings define an important mechanism for proteasome regulation and demonstrate the biological significance of proteasome phosphorylation in regulating cell proliferation and tumorigenesis.